Tackling HIV in India : Evidence-Based Priority Setting and Programming - Claeson, M. (2012)
In the wake of a downward revision of the number of HIV-infected people, India is launching an ambitious US$2.5 billion, five-year HIV plan. Responding to new data on HIV prevalence and risk behavior, India has earmarked almost 70 percent of the budget for prevention; one-third focuses on prevention activities for those at highest risk of HIV, and the remainder addresses HIV testing expansion and services for pregnant women. About 20 percent of the total budget is for care and treatment. Although the size and scope of the proposed HIV response pose challenges, the world has much to learn from India's data-informed approach to policy and priority setting.